2020
DOI: 10.1038/s41598-020-60713-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of glass micro-electrodes for local electric field, electrical conductivity, and pH measurements

Abstract: In micro- and nanofluidic devices, liquid flows are often influenced by ionic currents generated by electric fields in narrow channels, which is an electrokinetic phenomenon. Various technologies have been developed that are analogous to semiconductor devices, such as diodes and field effect transistors. On the other hand, measurement techniques for local electric fields in such narrow channels have not yet been established. In the present study, electric fields in liquids are locally measured using glass micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
2
13
0
Order By: Relevance
“…As Pergel et al 43 indicated a possibility of steady-state measurements as well as equilibrium conditions, the present study also improved the pH resolution by applying galvanostatic currents. 37 In this study, we found that PEG solutions filled in the tips effectively work to increase ΔV which contributes to high-pH resolutions compared with the case of no stuffing materials in the tips. Furthermore, stability and reproducibility of electrical potential responses were clearly improved.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…As Pergel et al 43 indicated a possibility of steady-state measurements as well as equilibrium conditions, the present study also improved the pH resolution by applying galvanostatic currents. 37 In this study, we found that PEG solutions filled in the tips effectively work to increase ΔV which contributes to high-pH resolutions compared with the case of no stuffing materials in the tips. Furthermore, stability and reproducibility of electrical potential responses were clearly improved.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…Instrumentation developed to measure conductivity is based on: induction, [87][88][89][90][91] potentiometry [92] with Pt electrodes, [92] microneedles, [93,94] gold-coated glass electrodes, [95] and local electric fields. [96]…”
Section: Conductivity and Phmentioning
confidence: 99%
“…The tip size of the microelectrode is 1 μm or less, and the spatial resolution is expected to be comparable to the tip size. The test section in a liquid vessel is well designed to maintain uniform electric fields . Using a motorized stage, the microelectrode is swept along the channel with a step varied from 20 to 200 μm.…”
Section: Introductionmentioning
confidence: 99%
“…The test section in a liquid vessel is well designed to maintain uniform electric fields. 25 Using a motorized stage, the microelectrode is swept along the channel with a step varied from 20 to 200 μm. This direct measurement of local electric fields enables us to evaluate the conductivity or concentration without calibration.…”
Section: Introductionmentioning
confidence: 99%